2024
DOI: 10.1101/2024.05.29.24308155
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Artificial Intelligence in Periodontology: Performance Evaluation of ChatGPT, Claude, and Gemini on the In-service Examination

Bushra Ahmad,
Khaled Saleh,
Saleh Alharbi
et al.

Abstract: BackgroundArtificial intelligence (AI) language models have shown potential as educational tools in healthcare, but their accuracy and reliability in periodontology education require further evaluation. In this study we aimed to assess and compare the performance of three prominent AI language models—ChatGPT-4o, Claude 3 Opus, and Gemini Advanced—with second-year periodontics residents across the United States on the American Academy of Periodontology 2024 in-service examination.MethodsWe conducted a cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…[39,40] Recent studies have demonstrated promising applications in periodontal disease management, including predicting treatment outcomes, detecting disease from radiographs, and identifying high-risk individuals. [10,41,42] Our findings further highlight the importance of integrating medical and dental care by demonstrating that routine blood tests can predict the risk of developing periodontitis. This machine learning model provides a valuable tool for early detection and prevention of periodontitis in primary care and non-dental healthcare settings.…”
Section: Discussionmentioning
confidence: 59%
“…[39,40] Recent studies have demonstrated promising applications in periodontal disease management, including predicting treatment outcomes, detecting disease from radiographs, and identifying high-risk individuals. [10,41,42] Our findings further highlight the importance of integrating medical and dental care by demonstrating that routine blood tests can predict the risk of developing periodontitis. This machine learning model provides a valuable tool for early detection and prevention of periodontitis in primary care and non-dental healthcare settings.…”
Section: Discussionmentioning
confidence: 59%